Profile of potential organ donors in a reference hospital - Thamy Braga Rodrigues; Maristela Inês Osawa Chagas; Maria da Conceição Coelho Brito; Diane Sousa Sales; Regina Célia Carvalho da Silva; Ângela Maria Alves e Souza (Universidade Federal do Ceará, 2013)
The study aimed to characterize the profile of potential organ donors in a hospital in the northern zone of Ceará, Brazil. This is a quantitative, retrospective and documentary study, performed in a hospital of Ceará, from information contained in the medical records of potential donors, from May to September 2009. Data were tabulated, focusing on the identification process and logistic aspects. We identified that the most prevalent diagnoses were traumatic brain injury (51.4%) and stroke (31.4%), and that 57.1% completed the process in time for organ procurement. Thus, we hope that the assessment of policy and donation data contributes to increase the donation rates, supporting the recognition of the process's weaknesses, as well as the implementation of measures to promote its success.